Efektivitas Cyber Public Relation Dinas Kesehatan Kota Bogor Terkait Informasi Covid-19 Terhadap Pemenuhan Kebutuhan Informasi Kesehatan Masyarakat - Ane Sajahwa; Roni Jayawinangun; Layung Paramesti Martha; Tiara Puspanidra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to determine the Effectiveness of Cyber PR for Covid-19 Information from the Bogor City Health Office in meeting the public's need for health information. This study uses a quantitative research approach. The data in this study were collected using a closed questionnaire which was then analyzed by multiple linear regression by SPSS 24. The results showed that the fulfillment of Cyber Information Needs at the Bogor City Health Office was included in the Good category. The cyber PR media owned by the Bogor City Health Office is a means or equipment used by the Bogor City Health Office in disseminating information about health during the pandemic to meet the information needs of the community. In this case, the people of Bogor City prefer to find out directly to the cyber media of the Bogor City Health Office as a reference in finding information about health because people feel that the Bogor City Health Office provides complete and varied information and is clear in conveying information.